2014
DOI: 10.5194/hess-18-2521-2014
|View full text |Cite
|
Sign up to set email alerts
|

Kalman filters for assimilating near-surface observations into the Richards equation – Part 2: A dual filter approach for simultaneous retrieval of states and parameters

Abstract: Abstract. This study presents a dual Kalman filter (DSUKF -dual standard-unscented Kalman filter) for retrieving states and parameters controlling the soil water dynamics in a homogeneous soil column, by assimilating near-surface state observations. The DSUKF couples a standard Kalman filter for retrieving the states of a linear solver of the Richards equation, and an unscented Kalman filter for retrieving the parameters of the soil hydraulic functions, which are defined according to the van Genuchten-Mualem c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…At longer term, the interest would be to enlarge the scope of the soil water and heat transfer model to other processes such as root uptake, solute transport, biogeochemical reaction and soil property dynamics. It was found that the main challenge in implementing a physically based model to estimate soil water content is the evaluation of soil hydraulic properties, requiring the development of estimation strategies such as using pedotransfer functions (PTF) and assimilation techniques (Witono and Bruckler, 1989;Zhu and Mohanty, 2004;Medina et al, 2014). Our work focuses on the innovation made in the FHAVeT (Fast Hydro Atmosphere Vegetation Temperature) model and does not consider those strategies that are already addressed in other studies (Chanzy et al, 2008).…”
Section: -J Tinet Et Al: Development and Evaluation In Bare Soil Comentioning
confidence: 99%
“…At longer term, the interest would be to enlarge the scope of the soil water and heat transfer model to other processes such as root uptake, solute transport, biogeochemical reaction and soil property dynamics. It was found that the main challenge in implementing a physically based model to estimate soil water content is the evaluation of soil hydraulic properties, requiring the development of estimation strategies such as using pedotransfer functions (PTF) and assimilation techniques (Witono and Bruckler, 1989;Zhu and Mohanty, 2004;Medina et al, 2014). Our work focuses on the innovation made in the FHAVeT (Fast Hydro Atmosphere Vegetation Temperature) model and does not consider those strategies that are already addressed in other studies (Chanzy et al, 2008).…”
Section: -J Tinet Et Al: Development and Evaluation In Bare Soil Comentioning
confidence: 99%
“…However, several studies highlighted the instability and intractability of this approach as a result of the complex interactions between states and parameters in a nonlinear dynamic system (Moradkhani et al, 2005;Liu and Gupta, 2007). Medina et al (2014) have shown that the decoupled state-space representation in the dual KF provides higher flexibility since different Kalman filters can be selected for the states and parameters, respectively, according to the specific characteristics of both the observation and system equations.…”
Section: H Medina Et Al: Part 3: Retrieving States and Parameters Fmentioning
confidence: 99%
“…Nevertheless, further improvements can be easily incorporated, as for instance reported by Kavetski et al (2002), who demonstrated that the reliability and the efficiency of these noniterative linearized schemes can be increased by adaptive truncation error control, and can be even more efficient than analogous time stepping schemes with iterative solvers. Medina et al (2014) provided valuable insights about the identifiability of the parameters featuring in the van Genuchten-Mualem soil hydraulic analytical relations (van Genuchten, 1980) by means of dual Kalman filters. This study also discussed the impact exerted by parameter initialization, observation depth, and assimilation frequency on the overall DSUKF retrieval performance, as well as the influence of the formulation of the Richards differential equation (either h-based or θ-based form).…”
Section: H Medina Et Al: Part 3: Retrieving States and Parameters Fmentioning
confidence: 99%
See 2 more Smart Citations